Anti-Malignant Effect of Tensile Loading to Adherens Junctions in Cutaneous Squamous Cell Carcinoma Cells - Dobrokhotov, Oleg; Sunagawa, Masaki; Torii, Takeru; Mii, Shinji; Kawauchi, Keiko; Enomoto, Atsushi; Sokabe, Masahiro; Hirata, Hiroaki (Frontiers in Cell and Developmental Biology, 2021)
Actomyosin contractility regulates various cellular processes including proliferation and differentiation while dysregulation of actomyosin activity contributes to cancer development and progression. Previously, we have reported that actomyosin-generated tension at adherens junctions is required for cell density-dependent inhibition of proliferation of normal skin keratinocytes. However, it remains unclear how actomyosin contractility affects the hyperproliferation ability of cutaneous squamous cell carcinoma (cSCC) cells. In this study, we find that actomyosin activity is impaired in cSCC cells both in vitro and in vivo. External application of tensile loads to adherens junctions by sustained mechanical stretch attenuates the proliferation of cSCC cells, which depends on intact adherens junctions. Forced activation of actomyosin of cSCC cells also inhibits their proliferation in a cell-cell contact-dependent manner. Furthermore, the cell cycle arrest induced by tensile loading to adherens junctions is accompanied by epidermal differentiation in cSCC cells. Our results show that the degree of malignant properties of cSCC cells can be reduced by applying tensile loads to adherens junctions, which implies that the mechanical status of adherens junctions may serve as a novel therapeutic target for cSCC.